An Exploration into the Nature of the Making of Human and Artifcial Intelligence and the Qur’anic Persepctive (American Journal of Islam and Society, 1992)
The ongoing controversy over artificial and human intelligence ischaracterized by open disagreement. Some researchers believe that artificialintelligence has the potential to become equal to or even superior tohuman intelligence, while others say that such a development is impossible.The thesis of this paper is that the gap between human and artificialintelligence is bound to remain considerable, both in the short term andin the long term. The concepts of human cultural symbols and theQur’anic vision of human intelligence are intduced in support of thisthesis. Humanity’s ability to manipulate cultural symbols, upon which thephenomenon of human intelligence depends, is a uniquely human characteristic.And this uniqueness, according to the Qur’an, is the direct resultof a divine decision, not of evolution. As such an ability and many of themysteries of that power, are hardly accessible to humans, how wouldhuman researchers be able to include them in the design of artificial intelligencemachines?In the last two decades, research in the field of artificial intelligence(hereinafter referred to as AI) has made considerable headway on both thetheoretical and the applied levels. The input into the field has not beenrestricted only to cybernetics and information process experts; neurophysiologists,cognitive psychologists, philosophers, and sociologists’ havealso been interested in human intelligence (hereinafter referred to as HI)and AI. As AI infrastructures and authority continue to expand in modemand postmodem societies, specialists in other areas will have to becomeinvolved.For scientists, basic and applied research into A1 constitute an exciting ...